2022
DOI: 10.1038/s41598-021-03360-2
|View full text |Cite|
|
Sign up to set email alerts
|

Microwave-assisted enzymatic hydrolysis to produce xylooligosaccharides from rice husk alkali-soluble arabinoxylan

Abstract: The prebiotic properties of xylooligosaccharides (XOS) and arabino-xylooligosaccharides (AXOS) produced from rice husk (RH) using microwave treatment combined with enzymatic hydrolysis were evaluated. The RH was subjected to microwave pretreatment at 140, 160 and 180 °C for 5, 10 and 15 min to obtain crude arabinoxylan (AX). Increasing microwave pretreatment time increased sugar content. Crude AX was extracted with 2% (w/v) sodium hydroxide at 25 °C for 24 h and used as a substrate for XOS production by commer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The hydrolysis of cassava pulp has been reported based on various approaches, such as acid hydrolysis ( Phowan and Danvirutai, 2014 ; Kurdi and Hansawasdi, 2015 ), enzymatic hydrolysis ( Bunterngsook et al, 2017 ; Siriwong et al, 2019 ), and a combination of acid and enzymatic hydrolysis ( Thongchul et al, 2010 ; Wattanagonniyom et al, 2017 ; Efeovbokhan et al, 2019 ; Areepak et al, 2022 ). Recently, microwave-assisted hydrolysis has gained some interest as it is an express and simple method for adopting biorefineries ( Tsubaki et al, 2008 ; Hermiati et al, 2012 ; Klangpetch et al, 2022 ). In this study, household microwaves were chosen and tested for their potential use in microwave-assisted hydrolysis strategies due to their price and easy operation.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolysis of cassava pulp has been reported based on various approaches, such as acid hydrolysis ( Phowan and Danvirutai, 2014 ; Kurdi and Hansawasdi, 2015 ), enzymatic hydrolysis ( Bunterngsook et al, 2017 ; Siriwong et al, 2019 ), and a combination of acid and enzymatic hydrolysis ( Thongchul et al, 2010 ; Wattanagonniyom et al, 2017 ; Efeovbokhan et al, 2019 ; Areepak et al, 2022 ). Recently, microwave-assisted hydrolysis has gained some interest as it is an express and simple method for adopting biorefineries ( Tsubaki et al, 2008 ; Hermiati et al, 2012 ; Klangpetch et al, 2022 ). In this study, household microwaves were chosen and tested for their potential use in microwave-assisted hydrolysis strategies due to their price and easy operation.…”
Section: Discussionmentioning
confidence: 99%
“…Microwave treatment causes fragmentation and swelling, leading to the degradation of lignin and hemicellulose, thereby improving pentose yield. Results have shown that microwave pretreatment is a promising method for lignocellulosic degradation of rice husks [53]. Microwave-assisted reactions significantly decrease xylose content in hydrolysates and greatly increase the yield of XOs compared to conventional heating methods [54].…”
Section: Lignocellulosic Biomass Pretreatmentmentioning
confidence: 99%